Geomorphological-related heterogeneity as reflected in tree growth and its relationships with climate of Monte Desert Prosopis flexuosa DC woodlands - Piraino, Sergio (2015)
Key message: Across the Central Monte Desert district in Argentina, landform and soil variability drive radial growth ofProsopis flexuosaand its relation with precipitation. Abstract: Desert forests grow under diverse ecological conditions, mainly resulting from the spatial heterogeneity of drylands with consequences on tree growth and its interactions with climate. In the Monte Desert, geomorphological processes generate landform and soil variability, determining the distribution and growth of plant species. Prosopis flexuosa DC., a dominant tree species in the Central Monte Desert, grows in territories characterized by a high variability of landform and soil. We applied classical dendrochronological and statistical analysis to disentangle the effect of spatial heterogeneity upon the species radial growth and its further relation with precipitation fluctuations. Trees from 11 plots distributed in seven P. flexuosa forests encompassing the most important geomorphological/landform units in the Central Monte Desert were analyzed. Tree-ring development at both high and low frequencies reflects spatial landform variability. Soil heterogeneity drives ring growth within landform. Regionally, precipitation influences radial growth at the beginning and the end of the growing season, while locally dependent mechanisms related to landform/soil variability emerged. In this sense, the negative influence of late-summer precipitation found for a riparian chronology is a function of soil permeability. Ring growth at the paleo-river environment depends on late spring and early mid-summer precipitation, with within-landform differences probably related to soil heterogeneity. In the case of inter-dune and lowland units, radial growth depends on early spring rainfall. Our findings highlight the influence of the heterogeneity of desert environments on tree growth. The information is relevant to management and conservation policies, particularly for the forests of P. flexuosa in Argentine Monte.